The role of the slope of oxygen consumption and EMG activity on freely chosen pedal rate selection - Bessot, N.; Moussay, S.; Laborde, S.; Gauthier, A.; Sesboüé, B. (European Journal of Applied Physiology, 2008)
The objective of this study was to verify the following hypothesis: the pedal rate that minimizes root mean square (RMS) slope and the slow component amplitude of oxygen consumption could be close to the freely chosen pedal rate (FCPR) used by well-trained cyclists. Nine male competitive cyclists performed a 21 min submaximal exercise on a cycle ergometer at a workload of 65% of their respective peak aerobic power. For each session, the subject`s pedal rate was freely chosen or assigned to 60, 75, 90 or 105 rev min-1. When pedal rates were imposed, the electromyographic root mean square slope, the oxygen uptake during the third minute and the 20th min, and the slow component amplitude of oxygen consumption were used in the analysis. In order to determine the optimal pedal rate (OPR), a quadratic function was fitted to the data by regression, for each variable measured. The mean values of OPR relative to oxygen uptake during the third min (71 ± 9 rev min-1) were lower than the mean values of the OPR relative to the slow component amplitude of oxygen consumption (82 ± 8 rev min-1), the electromyographic root mean square slope (80 ± 7 rev min-1) and freely chosen pedal rate (86 ± 13 rev min-1). Freely chosen pedal rate was not significantly different from the OPR in reference to the amplitude of the slow component of oxygen consumption, electromyographic root mean square slope, and oxygen uptake during the 20th min. OPR for RMS slope was correlated (R = 0.72) to FCPR. Expert cyclists were likely to use a spontaneous pedal rate that minimizes neuromuscular fatigue.